LAND SURFACE CHANGES DUE TO BUKITTINGGI CITY EARTHQUAKE USING THE 2019-2020 DInSAR METHOD - Saiyidinal Fikri; Desi Syafriani; Fitra Hasanah (JICE (Journal of Infrastructural in Civil Engineering), 2022)
Bukittinggi city is in the sink segmentation "semangko" fault line, which causes Bukittinggi City to frequently experience earthquakes. From 2019 to 2020, there have been at least 9 earthquakes above 5 on the Richter scale. DInSAR is a radar imaging method that utilizes phase, amplitude, and wavelength in its processing to obtain topography and land surface changes. This study has three aims. This research shows that the earthquake from 2019 to 2020 uses 18 pairs of sentinel-1 image scans recorded in 2019-2020 and uses DEM SRTM 30, namely the earthquake that happened on February 2, 2019, in the sub-district of Guguak Panjang with a range of 1 – 45 mm. The smallest increase occurred in the sub-district of Guguak Panjang and Mandiangin Koto Selayan, with a length of 1 mm on November 11, 2019. The most significant reduction happened in the sub-district of Aur Birugo with -22 mm. In contrast, a less substantial reduction occurred in the sub-district of Guguak Panjang with -5 mm on October 8, 2019. The Modified Mercalli intensity scale for earthquakes in 2019-2020 uses the measure of Donovan's parameters demonstrated by numbers 2, 3, and 4. Number 2 indicates that resting people feel the earthquake's strength, especially hanging, shaking, and vibrating on the second floor. Number 3 represents the vibrations of passing trucks, windows, doors, and glassware clashing and making noises